Sox2 in the dermal papilla niche controls hair growth by fine-tuning Bmp signaling in differentiating hair shaft progenitors - Clavel, Carlos (2012)
How dermal papilla (DP) niche cells regulate hair follicle progenitors to control hair growth remains unclear. Using Tbx18(Cre) to target embryonic DP precursors, we ablate the transcription factor Sox2 early and efficiently, resulting in diminished hair shaft outgrowth. We find that DP niche expression of Sox2 controls the migration rate of differentiating hair shaft progenitors. Transcriptional profiling of Sox2 null DPs reveals increased Bmp6 and decreased Bmp inhibitor Sostdc1, a direct Sox2 transcriptional target. Subsequently, we identify upregulated Bmp signaling in knockout hair shaft progenitors and demonstrate that Bmps inhibit cell migration, an effect that can be attenuated by Sostdc1. A shorter and Sox2-negative hair type lacks Sostdc1 in the DP and shows reduced migration and increased Bmp activity of hair shaft progenitors. Collectively, our data identify Sox2 as a key regulator of hair growth that controls progenitor migration by fine-tuning Bmp-mediated mesenchymal-epithelial crosstalk.